SEKTOR RIIL DAN KEUANGAN SYARIAH SERTA PENGARUHNYA TERHADAP PERTUMBUHAN EKONOMI REGIONAL SUMATERA UTARA TAHUN 2015 – 2019 - Ainun Khofifah; Andri Soemitra; Khairina Tambunan (LPPM Universitas Malikussaleh – Indonesia, 2021)
This research is a quantitative study. The data used is sourced from CSA (Central Statistics Agency) North Sumatra and FSA (Financial Services Authority). The analysis used in this research is multiple linear regression analysis with method Ordinary Least Square using program EVIEWS 8. The results showed that: 1) the Real Sector significantly positively affected the Regional Economic Growth of the North Sumatra Region with a probability value of 0.0000 less than the significant level (5%) or 0.0000<0.05. 2) Islamic Finance significantly positively affects the Regional Economic Growth of the North Sumatra Region with a probability value of 0.0000 less than the significant level (5%) or 0.0000<0.05. 3) The results of the study simultaneously show that the Real Sector and Islamic Finance have a significant effect on the Regional Economic Growth of the North Sumatra Region with a probability value (F-statistics) less than the significant level (5%) or 0.0000<0.05. It can also be seen in the regression of the R-Square value which shows that around 0.724519 or 0.72% of the Real Sector and Islamic Finance variables can explain the Regional Economic Growth of the North Sumatra Region in the 2015 – 2019 period, while the remaining 28% is explained by other variables.Keywords : GDP, Islamic Banking, Islamic Fianancing, North Sumatera, Real Sector, Regional Economic Growth, Trade sector